Culturally responsive assessment practices in ethnic minority semi-boarding primary schools in Vietnam: a mixed-methods study - Duong, Lam Thuy; Khuong, Phi Dinh (Frontiers in Education, 2025)
This study examines the implementation and determinants of culturally responsive assessment (CRA) in ethnic minority semi-boarding primary schools in Vietnam. Four structured questionnaires were distributed to school leaders (n = 123), teachers (n = 406), parents (n = 523), and students (n = 7,788), yielding 1,006 valid returns; after quality screening, the final analytic sample comprised 778 respondents. Adopting a mixed-methods design, we applied Partial Least Squares Structural Equation Modeling (PLS-SEM) and Importance–Performance Map Analysis (IPMA), alongside thematic analysis of open-ended responses. The structural model explained a substantial share of variance in Behavioral Intention (R2 = 0.735). Attitude emerged as the strongest predictor (β = 0.801, p < 0.001), underscoring the central role of stakeholders' dispositions toward CRA; IPMA identified a high-importance/low-performance gap for Support, signaling a priority area for intervention. Qualitative evidence—such as students' preference for oral storytelling and parents' involvement in assessment design—corroborated the quantitative patterns and enhanced methodological transparency. The study contributes to CRA scholarship by consolidating evidence from Vietnam and Southeast Asia, linking CRA with culturally sustaining pedagogies, and offering actionable guidance for practice and policy. Practical implications include embedding CRA principles in teacher preparation, co-developing community-based assessment materials, and fostering professional learning communities. The findings provide a replicable framework for advancing equity and inclusivity in linguistically and culturally diverse schooling contexts.